BIG-DATA SKILLS: BRIDGING THE DATA SCIENCE THEORY-PRACTICE GAP IN HEALTHCARE. - Dolezel, Diane; McLeod, Alexander (Perspectives in Health Information Management)
Demand for big-data scientists continues to escalate driving a pressing need for new graduates to be more fluent in the big-data skills needed by employers. If a gap exists between the educational knowledge held by graduates and big data workplace skills needed to produce results, workers will be unable to address the big data needs of employers. This survey explores big-data skills in the classroom and those required in the workplace to determine if a skills gap exists for big-data scientists. In this work, data was collected using a national survey of healthcare professionals. Participant responses were analyzed to inform curriculum development, providing valuable information for academics and the industry leaders who hire new data talent.